유무인 협업 기반 효과적인 공대공 작전 절차 및 평가 모델 - 이태균 (The Graduate School, Ajou University, 2024)
Manned and unmanned collaboration operations in the air domain are recognized as an essential element in future warfare, and much research is being conducted. As part of the 3rd offset strategy, in which the United States designates autonomous weapon systems applying 4th industrial revolution technologies such as big data and artificial intelligence as its main force, and the U.S. Department of Defense and each military announces a roadmap emphasizing the role of autonomous systems. Therefore, the future aerial battlefield is expected to develop into a situation where manned and unmanned aircraft teams operate together with manned aircraft and artificial intelligence unmanned aerial aircraft. Through this, even if necessary decisions during mission performance are made by human pilots, other necessary functions will be possible to operate as an unmanned aircraft. Therefore, it is a very important issue how to organize a manned and unmanned aircraft team for mission success and assign the team to a mission that can overwhelm the enemy to improve the possibility of survival in the mission._x000D_ This paper presents future manned and unmanned aircraft collaboration-based air-to-air operation procedures and an operational evaluation model that can evaluate them. In the future, ‘operational agility’ that can quickly produce various solutions to a given situation is expected to be required. The air-to-air operation procedure based on manned and unmanned aircraft collaboration enabled a shorter operation procedure than the existing procedure by speeding up the operation tempo through sharing common situational awareness. To verify the effectiveness of the operational procedure, we propose an operational evaluation model based on Lanchester's law that can predict the results of air-to-air engagements. To evaluate combat power, a relative combat power index calculation method was applied, through which the relative combat power index of enemy and friendly aircraft was calculated and then substituted into the evaluation model to predict the outcome of the engagement._x000D_ As a result of numerical analysis of the operational model, the actual training data and the predictions of the proposed model were similar, confirming the effectiveness of the proposed model. In addition, in the evaluation of effectiveness in terms of the number of weapons consumed during an engagement and the number of aircraft deployed, it was confirmed that the effectiveness of the air-to-air operation procedure based on manned and unmanned aircraft collaboration was superior to the existing procedure.|공중 영역에서 유·무인 협업(Manned and Unmanned Collaboration) 작전은 미래전의 필수적인 요소로 인식되어 많은 연구가 이뤄지고 있다. 이는 미국이 3차 상쇄전략(Offset Strategy)으로 빅데이터, 인공지능 등 4차 산업혁명 기술을 적용한 자율 무기체계를 주요 전력으로 지정한 것을 배경으로 한다. 이에 따라 미 국방부와 각 군들은 자율 체계의 역할을 강조하는 로드맵을 발표했다. 따라서 미래 공중 전장은 유인전투기와 인공지능 무인전투기가 함께 운용되는 유·무인전투기 팀이 작전하는 모습으로 발전이 예상된다. 이를 통해 임무 수행 중 필요한 결정은 인간 조종사에 의해 판단되더라도 이외 필요한 기능은 무인전투기로 운용이 가능할 것이다. 그러므로 임무 성공을 위하여 유·무인전투기 팀을 어떻게 구성할 것인지와 임무에서의 생존 가능성 향상을 위해 그 팀을 적을 압도할 수 있는 임무에 배정하는 것은 매우 중요한 문제이다._x000D_ 본 논문에서는 미래의 유·무인전투기 협업 기반 공대공 작전 절차와 이를 평가할 수 있는 작전 평가 모델을 제시한다. 미래에는 주어진 상황에 대해 다양한 해결책을 빠르게 생산할 수 있는 ‘작전적 민첩성’이 요구될 것으로 보인다. 유·무인전투기 협업 기반 공대공 작전 절차는 임무 편조 내 공통된 상황인식 공유를 통해 작전 템포를 빠르게 하여 기존 공대공 작전 절차보다 단축된 작전 절차가 가능했다. 작전 절차의 유효성을 검증하기 위해 공대공 교전 결과를 예측할 수 있는 란체스터 법칙을 기반으로 작전 평가 모델을 제안한다. 전투력 평가를 위해 상대적 전투력 지수 산정 방식을 적용했고, 이를 통해 적군과 아군 전투기의 상대적 전투력 지수를 계산 후 평가 모델에 대입하여 교전 결과를 예측했다._x000D_ 작전 모델에 대한 수치 분석 결과, 실제 훈련 데이터와 제안 모델의 예측이 유사하여 제안 모델이 효과성이 있음을 확인했다. 또한 교전 시 소모된 무장의 수와 투입된 전투기 수에서의 효과성 평가에서도 유·무인전투기 협업 기반 공대공 작전 절차 시 기존 절차보다 효과성이 뛰어난 것을 확인했다.
학위논문(석사)--국방디지털융합학과,2024. 2
Keywords: 공대공 작전(Air-to-Air operations); 공중 유무인 협업(Aerial manned and unmanned collaboration); 란체스터 법칙(Lanchester's law)